Teaching world languages in middle and secondary schools : a critical introduction - Reagan, Timothy; Osborn, Terry A. (Emerald Publishing Limited, 2025)
Teaching World Languages in Middle and Secondary Schools: A Critical Introduction is an introductory textbook for teacher education candidates, at either the undergraduate or graduate levels, who are seeking certification to teach a world/foreign language. It might also be used as a methods textbook in programs preparing teachers to work with English Language Learners (ELLs) in public school contexts. There is a growing shortage of world language teachers in the United States, and the market for such educators is likely to increase dramatically in the years ahead. Currently, only about 20% of US students study a language other than English, although this may change if more individuals are prepared to teach world languages. This book stands out from most world language education methodology books by combining ideas, concepts, and practices from two traditions in the world language education literature that rarely overlap: the technical skills and knowledge needed to be an effective and competent classroom teacher, and the growing literature on critical pedagogy in the specific context of world language education.
Includes index.
Keywords: Language and languages -- Study and teaching.; Education -- Teaching -- Subjects -- General.; Language teaching and learning.; Teaching of a specific subject.; elektronické knihy; electronic books